Effects of Dance Movement Therapy on the Mental Health of Chinese Higher Vocational Students—Taking A Higher Vocational College as an Example - Yao, Chen; Wen Wang, Shang (Journal of Roi Kaensarn Academi, 2023)
This study aims to explore the impact of Dance Movement Therapy on the mental health of Chinese higher vocational students. The experimental research is carried out on the students of A higher vocational college in Guizhou Province, and 50 students are selected as the experimental group by voluntary registration. At the same time 50 students were selected as the control group. After a semester of experimentation, the results of the study found that the posttest data of the experimental group and the posttest data of the control group had significant differences in the overall mental health scale and negative mental health dimensions, but the differences in the positive mental health dimensions were not significant. The difference between the pre-test data of the experimental group and the post-test data of the experimental group in the overall scale of mental health and the dimension of negative mental health was significant, but the difference in the dimension of positive mental health was not significant. However, there are significant differences in the overall scale of mental health, indicating that therapeutic dance courses can promote the mental health of higher vocational students.